Perspectivas de la enseñanza de la filosofía en Costa Rica: el caso de la Universidad Nacional - Gómez Torres, Juan (2012)
This article to discuss the possible traces of teaching of philosophy in a globalized world discursively presented as reasonable, but which in practice is determined by an instrumentalist character of reason. This context, among others, claiming the importance of learning to think, to philosophize and to transform, however, this task is not easy, and requires a rigorous education that originates from research and training processes